2006
DOI: 10.1038/sj.npp.1301230
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Changes in Gαolf Protein Levels, but not D1 Receptor, Alter Specifically Acute Responses to Psychostimulants

Abstract: Striatal dopamine D1 receptors (D1R) are coupled to adenylyl cyclase through Gaolf. Although this pathway is involved in important brain functions, the consequences of quantitative alterations of its components are not known. We explored the biochemical and behavioral responses to cocaine and D-amphetamine (D-amph) in mice with heterozygous mutations of genes encoding D1R and Gaolf (Drd1a + /À and Gnal + /À), which express decreased levels of the corresponding proteins in the striatum. Dopamine-stimulated cAMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 58 publications
8
53
0
Order By: Relevance
“…This observation was particularly interesting, as in these mice the levels of Ga olf are decreased by approximately 50% (cf. Figure 5a), which results in a large reduction of cAMP signaling (Corvol et al, 2007). Taken together, these results indicate that haloperidol increases rpS6 phosphorylation by removing the inhibitory tone normally exerted by D2Rs on A2AR-mediated cAMP production.…”
Section: Haloperidol-induced Phosphorylation Of Rps6 Depends On Adenomentioning
confidence: 48%
See 1 more Smart Citation
“…This observation was particularly interesting, as in these mice the levels of Ga olf are decreased by approximately 50% (cf. Figure 5a), which results in a large reduction of cAMP signaling (Corvol et al, 2007). Taken together, these results indicate that haloperidol increases rpS6 phosphorylation by removing the inhibitory tone normally exerted by D2Rs on A2AR-mediated cAMP production.…”
Section: Haloperidol-induced Phosphorylation Of Rps6 Depends On Adenomentioning
confidence: 48%
“…We found that blockade of A2ARs with 3 mg/kg of KW6002 reduced the effect of haloperidol on phospho-Ser235/236-rpS6 (Figure 4a and b). A similar decrease in haloperidol-induced rpS6 phosphorylation was observed in Gnal + /À mice carrying a Haloperidol regulation of ribosomal protein rpS6 E Valjent et al heterozygous mutation of the gene encoding for Ga olf , which reduces the levels of this protein in the striatum (Corvol et al, 2007) (Figure 5). This observation was particularly interesting, as in these mice the levels of Ga olf are decreased by approximately 50% (cf.…”
Section: Haloperidol-induced Phosphorylation Of Rps6 Depends On Adenomentioning
confidence: 64%
“…Because this receptor utilizes the same G-protein ␣ olf ␤ 2 ␥ 7 heterotrimer (6), it will be interesting to explore whether poor coupling of the D 1 R is also observed in the striatum and whether the G olf represents the rate-limiting step in adenylyl cyclase activation. Supporting the latter possibility, our previous analyses of mutant Drda1a and Gnal mice have revealed that the G-protein rather than the receptor controls psychostimulant responses (60).…”
Section: Discussionmentioning
confidence: 60%
“…The connection to D1 signaling is complex, however, as comparisons between heterozygous Gα olf (representing the likely molecular situation in DYT25) and D1 dopamine receptor mice show several interesting differences at the molecular and behavioral level. For example, Gα olf heterozygous mice show a decreased behavioral response and cAMP increase to cocaine or D-amphetamine, whereas similar behavioral changes are not observed in D1 receptor heterozygous mice [106,111]. These and related differences (reviewed in detail in Herve [104]), and the role of Gα olf in A2A signaling and in cholinergic neurons, highlight the need for further studies identifying which of these roles (or combination of effects) is key for dystonia pathogenesis.…”
Section: Dyt25 (Gnal)mentioning
confidence: 99%
“…Gα olf null mice are hyperactive at baseline, implicating loss of Gα olf with a hyperkinetic state [108]. These mice show marked deficiencies in locomotor and molecular responses linked to D1 activation, including a blunted increase in movement to D1 agonists or acute cocaine, and reduced activation of cAMP, PKA, ERK or c-fos [109][110][111] following D1 treatment. This link to D1 signaling is particularly intriguing considering that D1 hypersensitivity is strongly implicated in L-dopa induced dyskinesias in Parkinson disease in connection with abnormal plasticity [112]-a pathogenic mechanism thought to be important in the pathogenesis of primary dystonia [113][114].…”
Section: Dyt25 (Gnal)mentioning
confidence: 99%